2010
DOI: 10.1093/jxb/erq177
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously induced expression of ethylene biosynthesis, ethylene perception, phospholipase D, and Rboh-oxidase genes in broccoli seedlings

Abstract: In higher plants, copper ions, hydrogen peroxide, and cycloheximide have been recognized as very effective inducers of the transcriptional activity of genes encoding the enzymes of the ethylene biosynthesis pathway. In this report, the transcriptional patterns of genes encoding the 1-aminocyclopropane-1-carboxylate synthases (ACSs), 1-aminocyclopropane-1-carboxylate oxidases (ACOs), ETR1, ETR2, and ERS1 ethylene receptors, phospholipase D (PLD)-α1, -α2, -γ1, and -δ, and respiratory burst oxidase homologue (Rbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 106 publications
3
35
0
Order By: Relevance
“…However, these two HMs increased ethylene levels in mustard plants by enhancing ACS activity . In other recent studies, Jakubowicz et al (2010) reported that 2.5 mM Cu induced ethylene biosynthesis in broccoli (Brassica oleracea) seedlings, and Franchin et al (2007) noted significantly enhanced ethylene production with Cu concentration within a range of 5 to 500 mM, causing leaf toxicity and impairing root formation in poplar (Populus alba). In contrast, Cu at 25 and 50 mM did not significantly induce ethylene production in Arabidopsis seedlings (Lequeux et al, 2010).…”
Section: Ethylene and Plant Responses To Hm Stressmentioning
confidence: 93%
“…However, these two HMs increased ethylene levels in mustard plants by enhancing ACS activity . In other recent studies, Jakubowicz et al (2010) reported that 2.5 mM Cu induced ethylene biosynthesis in broccoli (Brassica oleracea) seedlings, and Franchin et al (2007) noted significantly enhanced ethylene production with Cu concentration within a range of 5 to 500 mM, causing leaf toxicity and impairing root formation in poplar (Populus alba). In contrast, Cu at 25 and 50 mM did not significantly induce ethylene production in Arabidopsis seedlings (Lequeux et al, 2010).…”
Section: Ethylene and Plant Responses To Hm Stressmentioning
confidence: 93%
“…Another important aspect of NO's mode of ethylene regulation is through the regulation of the effect of hydrogen peroxide, the latter being an effective inducer of ethylene biosynthetic gene transcription. 46 NO is a highly reactive molecule that can directly trigger ROS-linked redox changes by targeting transition metals (e.g., Fe, Cu and Zn) of signaling proteins, receptors, enzymes, transcription factors, DNA and proteins containing thiol groups via various modifications such as tyrosine nitration, S-nitrosylation and metal nitrosylation. Given the importance of H 2 O 2 in many physiological contexts which have economic relevance, the modulation of ethylene via H 2 O 2 as well as NO needs further elucidation.…”
Section: No Effects On Post/harvest Qualitymentioning
confidence: 99%
“…Plant RBOHs consist of C-terminal region containing cytosolic FAD and NADPH-binding domains, six conserved transmembrane-spanning domains, and N-terminal extension containing two Ca 2+ -binding EF-hand motifs and phosphorylation target sites that are important for their activity (Kobayashi et al 2007;Oda et al 2010;Kimura et al 2012;Drerup et al 2013). Previous studies in Arabidopsis have revealed several regulatory mechanisms of RBOH proteins, which involve protein phosphorylation, Ca 2+ , calcium-dependent protein kinases (CDPKs), and phospholipase Dα1 (PLDα1) (Lin et al 2009;Monshausen et al 2009;Zhang et al 2009b;Jakubowicz et al 2010;Dubiella et al 2013;Drerup et al 2013). Mechanical stimulation of plant tissue can induce an increase in cytosolic Ca 2+ via an influx from the apoplast across the plasma membrane (Monshausen et al 2009).…”
Section: Ros-generating Pathways and Their Regulatory Mechanisms In Pmentioning
confidence: 99%
“…Various forms of abiotic stress result in increased production of ROS which can be liked to signals caused by changes in the regulation of plant hormones (Fujita et al 2006). Ethylene biosynthesis was found to be modulated by positive regulation via RBOH proteins and negative regulation via CTR1 (constitutive triple response 1) (Jakubowicz et al 2010). In Arabidopsis, CTR1 can be inhibited by phosphatidic acid (PA) that positively enhances activation of RBOHD and RBOHF (Jakubowicz et al 2010).…”
Section: Ros Signaling Is Integrated With Various Other Signals Inclumentioning
confidence: 99%
See 1 more Smart Citation